Makna Hubungan Beda Agama Dalam Perspektif Islam Pada Film Akhirat A Love Story Karya Jason Iskandar - Dikri Assidiqi; Sayidah Afyatul Masruroh (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2023)
Film is an effective medium for conveying a message. But not every message can be conveyed properly; therefore, it is necessary to formulate the research problem: (1) What is the meaning of the sign of the relationship between different religions from an Islamic perspective in the film Akhirat: A Love Story? This study uses a qualitative approach, with the method used being Roland Barthes' semiotic analysis of